AB0516 Characteristics and treatment response of patients with axial spondyloarthritis (axspa) starting with sulfasalazine (ssz) or tnf-inhibitor (tnfi) as the first dmard. (23rd January 2014) - Fagerli, K. M.; van der Heijde, D.; Heiberg, M. S.; Rødevand, E.; Wierød, A.; Mikkelsen, K.; Kalstad, S.; Kvien, T. K.; Lie, E.
Abstract : Background: In the current recommendations for ankylosing spondylitis, SSZ is considered a treatment option in patients (pts) with peripheral disease (1 ), although it is widely accepted, and recently confirmed (2 ), that TNFi is superior to SSZ. Objectives: Characterize baseline differences in pts with axSpA who received TNFi or SSZ as their 1 st DMARD, and secondly, to compare the response to TNFi between pts who were DMARD naïve to those who had previously received SSZ. Methods: Data is from NOR-DMARD, a Norwegian multicentre observational study of pts receiving DMARDs. DMARD-naive pts with a clinical diagnosis of axSpA (ICD-10: M45, M46.1, M46.8 or M46.9) starting SSZ or a TNFi were included. Among the SSZ-pts, those who later switched to a TNFi were identified. Selected outcome measures were patient global, SF-6D and ASDAS, BASDAI and ASAS responses. For comparisons independent t-test, Mann-Whitney U test, and Chi-square test were used. Results: We included 181 pts receiving SSZ as their 1 st DMARD, of whom 66 later switched to a TNFi, and 543 pts receiving a TNFi as 1 st DMARD. Pts receiving SSZ as their 1 st DMARD were younger, more often female, had shorter disease duration and more swollen joints, but had similar disease activity (table ). At start of TNFi in the SSZ-switchers, disease duration and activity were similar to those who received TNFi as their 1 st DMARD (except more joint swelling). Response to TNFi was similar in the two groups (table ). Conclusions: The use of SSZ did not seem to delay treatment with TNFi, as disease duration and activity was similar in those receiving TNFi as 1 st DMARD and those who had first received SSZ, nor did response to TNFi appear to be impaired by prior SSZ-use. References: Braun J et al. Ann Rheum Dis 2011;70:896–904. Braun J e t al . J Rheumatol 2012;39:836-40. Disclosure of Interest: None Declared